1999
DOI: 10.1007/s004649900923
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic rectopexy according to Wells

Abstract: Laparoscopy was successful in all but one case. Follow-up is available in 32 of 37 patients. Prolapse was cured in all patients, and the incontinence resolved in 11 of 12. In addition, 38% of the patients experienced significant constipation preoperatively versus 5% postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 23 publications
2
27
0
1
Order By: Relevance
“…Athanasiadis et al [2] compared two groups operated on for rectal prolapse associated with constipation: 84% of the patients in the resection group were cured of, or experienced appreciable improvement in, their constipation, as compared with 8% in the rectopexy group. Other studies have confirmed these results, reporting improvements in constipation in 41-83% following rectopexy with partial resection of the colon, compared with 11-28% following rectopexy alone [19,38,43]. When resection alone resulted in the removal of a sufficient amount of redundant colon, a number of participating centers did not perform additional rectopexy.…”
Section: Discussionsupporting
confidence: 63%
“…Athanasiadis et al [2] compared two groups operated on for rectal prolapse associated with constipation: 84% of the patients in the resection group were cured of, or experienced appreciable improvement in, their constipation, as compared with 8% in the rectopexy group. Other studies have confirmed these results, reporting improvements in constipation in 41-83% following rectopexy with partial resection of the colon, compared with 11-28% following rectopexy alone [19,38,43]. When resection alone resulted in the removal of a sufficient amount of redundant colon, a number of participating centers did not perform additional rectopexy.…”
Section: Discussionsupporting
confidence: 63%
“…Fazio et al [19] reported similar results in their comparative study of laparoscopic Wells procedure and laparoscopic bowel resection with rectopexy. Good results have been obtained by other authors too [17,20]. The mechanism of continence recovery following surgery remains undetermined and no preoperative parameters are predictive.…”
Section: Discussionmentioning
confidence: 56%
“…Even though we are not able to confirm this notion, we do not believe that this conversion was directly imputable to the robotic approach. Sacral vein bleeding requiring conversion to open procedure has also been reported in laparoscopic series: Himpens et al [10] reported one conversion to laparotomy among 37 procedures because of this perioperative complication. Like Munz et al [18], who reported no morbidity in a short series of six patients operated on with robotic assistance to perform suture rectopexy, we believe that the robotic approach does not influence per-and postoperative morbidity whatever the performed procedure, if it is done exactly the same as in standard laparoscopy.…”
Section: Discussionmentioning
confidence: 93%